STORED COCOA BEANS QUALITY AFFECTED BY FERMENTATION AND EPHESTIA CAUTELLA WALKER (LEPIDOPTERA: PHYCITIDAE) INFESTATION - OKKY S. DHARMAPUTRA; SUNJAYA SUNJAYA; INA RETNOWATI; SANTI AMBARWATI (BIOTROPIA, 2000)
The effects of fermentation on Ephestia cautella population and cocoa beans quality in terms of moisture content, fungal population, the percentage of insect-damaged and mouldy beans, lipid and free fatty acid contents during storage were investigated together with the effects of £. cautella infestation on the quality of stored cocoa beans and weight loss. Fermented and unfermented cocoa beans with initial moisture contents of 7 or 9% were placed in ventilated plastic jars (Ikg/jar) and stored for 6 months under room conditions. Seven larvae of £. cautella instar IV (2 males and 5 females) were introduced in each jar at the beginning of storage. Untreated jars contained only cocoa beans. Population of £. cautella on fermented cocoa beans with either initial moisture content of 7 or 9% was lower than that on unfermented beans during storage. The population either on fermented or unfermented cocoa beans with initial moisture content of 7% was lower than that of 9%, and the population of all treatments increased during storage. Moisture content of all treatments either on cocoa beans with initial moisture contents of 7 or 9% had the same pattern. The percentage of insect-damaged beans on fermented cocoa beans was lower than that on unfermented cocoa beans after 5 to 6 months of storage. The damaged beans on fermented cocoa after 6 months of storage was not different than on unfermented beans after 4 months of storage. The weight loss either on fermented or unfermented cocoa beans with initial moisture content of 9% was higher than that with initial moisture content of 7%. The weight loss on fermented cocoa beans either with moisture content of 7 or 9% was lower than that on unfermented beans during storage. The weight loss either on fermented or unfermented cocoa beans increased during storage. The percentage of mouldy beans on cocoa infested with £. cautella tended to increase during storage, while on beans not infested with the insect it fluctuated during storage. The highest percentage of mouldy beans was on unfermented and infested cocoa beans. Twenty-one fungal species were isolated from all treatments of cocoa beans during storage. The total fungal population on fermented and unfermented beans had the same pattern. The population on fermented cocoa beans was lower than that on unfermented beans. Total l ipid content on fermented cocoa beans either infested or not with £. cautella having initial moisture content of 7 or 9%, was lower than that of unfermented beans. The content either on fermented or unfermented cocoa beans and either infested or not decreased during storage. Free fatty acid content on cocoa beans infested with £.  cautella was higher and significantly different than that on not infested. The content for both types increased during storage. Key Words :   Cocoa beans / Fermentation / Ephestia cautella I Moisture content / Fungal population / Insect-damaged beans / Mouldy beans / Lipid / Free fatty acid.